In Patients With Hypertension, the Cortical Perfusion Index Measured by Contrast Enhanced Ultrasound Reveals a Sexual Dimorphism - Aikaterini Damianaki; Mariëlle Hendriks‐Balk; Wendy Brito; Erietta Polychronopoulou; Kenji Theiler; Menno Pruijm; Grégoire Wuerzner (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Arterial hypertension is characterized by microvasculature changes and reduced tissue perfusion. It is unknown whether a sexual dimorphism of renal microcirculation is present in patients with arterial hypertension. We aimed to compare the cortical microcirculation in women and men with hypertension and to evaluate their response to sympathetic stimulation with a cold pressor test (CPT). Methods The cortical perfusion index (PI) measured by contrast‐enhanced ultrasonography was used as a proxy of renal microcirculation. We measured the PI at rest and during a 2‐minute CPT in patients with arterial hypertension. We used a linear mixed‐model analysis to study the effect of sex, the CPT, and their interaction on the PI. Results Thirty‐two participants were included (34% women). Age and body mass index were similar in both groups. Median PI was higher in women (2344 [interquartile range, 1553–2685 arbitrary units]) than men (1285 [interquartile range, 591–1741 arbitrary units], P=0.009). The CPT increased the PI in both groups; however, the magnitude of the response to CPT was similar in both sexes. Conclusions Women with arterial hypertension have a higher cortical microperfusion than men, while their microvascular reactivity to a CPT appears to be similar. This sexual dimorphism may have an impact on renal function decline, which needs further investigation.